Features of endodontic preparation of supporting teeth under the combined prosthetic appliances with a calculation on durability of structural chart of connections of the rigid and the semi-rigid system of fixation (LLC "Endo Press", 2020)
This article presents a calculation of the most aggressive zones of pressure of interlocking systems with rigid and semi-rigid locking system on the roots of the abutment teeth. Zones of maximum tension in the supporting teeth, as well as at the top of the top of the core inlay are indicated. Practical recommendations for the preparation of the first abutment tooth for core inlay are given, which eliminate aggressive expansion of the tooth channels. Gentle endodontic treatment will increase the diameter of the root wall in preparation for core inlay and to prevent breaking off the distal wall of the root. The most marked areas of tension of structures at making the combined prosthetics with a rigid system of fixed prostheses arise in the joint area of the castle with partial dentures. The use of semi-rigid fixing system eliminates the bending moment in the joint area of the locking system.